Fabrics-Shear Strength Links of Silicon-Based Granular Assemblies. (2nd December 2019) - Judes Sujatha, S.; Jahanger, Z. K.; Barbhuiya, S.; Antony, S. Joseph
Abstract : Silicon (Si)-based materials are sought in different engineering applications including Civil, Mechanical, Chemical, Materials, Energy and Minerals engineering. Silicon and Silicon dioxide are processed extensively in the industries in granular form, for example to develop durable concrete, shock and fracture resistant materials, biological, optical, mechanical and electronic devices which offer significant advantages over existing technologies. Here we focus on the constitutive behaviour of Si-based granular materials under mechanical shearing. In the recent times, it is widely recognised in the literature that the microscopic origin of shear strength in granular assemblies are associated with their ability to establish anisotropic networks (fabrics) comprising strong-force transmitting inter-particle contacts under shear loading. Strong contacts pertain to the relatively small number of contacts carrying greater than the average normal contact force. However, information on how such fabrics evolve in Si-based assemblies under mechanical loading, and their link to bulk shear strength of such assemblies are scarce in the literature. Using discrete element method (DEM), here we present results on how Si-based granular assemblies develop shear strength and their internal fabric structures under bi-axial quasi-static compression loading. Based on the analysis, a simple constitutive relation is presented for the bulk shear strength of the Si-based assemblies relating with their internal fabric anisotropy of the heavily loaded contacts. These findings could help to develop structure-processing property relations of Si-based materials in future, which originate at the microscale.